(3OQGSGJ GdLOhi GdJLGQjI hGdEbJUGOjI h GdGLJeGYjI eY eTQhYGJ (BBOTs - (3YHO GdbGOQ eMeO YHO GdbGOQ(B, (3YWjIs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2000)
(3OQGSGJ GdLOhi GdJLGQjI ddeTQhY(B:(3GdJYQja HOQGSGJ GdLOhi,OQGSI GdShb,GdJMdjd GdLOj debGQfI GdeTQhYGJ eGfYI GdJHGOd,GdLOhi GdJLGQjI, Jbhje GdeTQhYGJGdeSJbdI,GdJbhje GdbJUGOj(B-(3OQGSI GdLOhi GdGbJUGOjI,GdLOhi GdGbJUGOjIh GKQ GdJVNe,cjajI JUMjM dGSYGQ GdShbjI,GSYGQ GdXd dYfGUQ GdGfJGL,Jbhje GdeTQhYGJ aj Xd YOe GdJCcO (B-(3JMdjd GdLOhi GdGLJeGYjI,JMdjd GdGKGQ GdJfehjI ddeTQhY,fehPL JWHjbj ddeTQhYs
(3GdeQGLY U(B.825s
Keywords: (3GdeTGQjYs; (3OQGSI GdLOhis